Pengaruh Massage Olahraga Berbasis Pemulihan Terarah terhadap Adaptasi Fisik, Regulasi Emosi, dan Kesiapan Kompetitif Atlet - Salam, Agus; Helaprahara, Dian; Firdaus, Noer Wachid Riqzal (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aims to analyze the effect of directed recovery-based sports massage on physical adaptation, emotional regulation, and competitive readiness of athletes. This study uses a quantitative approach with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The study sample consisted of 30 athletes consisting of 11 soccer athletes, 9 male volleyball athletes, and 10 male futsal athletes. The research instrument used a Likert scale with 20 indicators representing four latent constructs: directed sports massage (MOT), physical adaptation (AF), emotional regulation (RE), and competitive readiness (KK). The results showed that directed sports massage had no significant effect on physical adaptation or emotional regulation. Physical adaptation was shown to have a positive and significant effect on emotional regulation, but did not significantly affect competitive readiness. Meanwhile, emotional regulation did not show a significant effect on competitive readiness of athletes. These findings indicate that sports massage has not provided a direct contribution to competitive readiness, and competitive readiness is more influenced by other factors outside the variables studied.